Combining tree-ring metal concentrations and lead, carbon and oxygen isotopes to reconstruct peri-urban atmospheric pollution - Annick Doucet (Tellus: Series B, Chemical and Physical Meteorology, 2012)
In this study, we analysed the tree-ring metal concentrations and isotope ratios of five stands located in three contrasted settings to infer the diffuse air pollution history of the northern part of the Windsor–Québec City Corridor in eastern Canada. Tree-ring series show that the Cd and Zn accumulation rates were higher between 1960 and 1986 and that the long-term acidification of the soil (Ca/Al series) was likely induced by NOx and SOx deposition (δ15N and δ13C trends as proxy). The Pb concentrations and 206Pb/207Pb ratios indicate that the dominant source of lead from 1880 to the 1920s was the combustion of north-eastern American coal, which was succeeded by the combustion of leaded gasoline from the 1920s to the end of the 1980s. Our modelling approach allows separating the climatic and anthropogenic effects on the tree-ring δ13C and δ18O responses. Diffuse air pollution caused an enrichment in 13C in all stands and a decrease of the δ18O values only in three of the stands. This study indicates that dendrogeochemistry can show contrasted responses to environmental changes and that the combination of several independent indicators constitutes a powerful tool to reconstruct the air pollution history in the complex context of peri-urban regions.